Peranan Desain Kemasan Produk dalam Meningkatkan Pemasaran Usaha Mikro Kecil Menengah (UMKM) pada Program Bedah Desain Kemasan 2023 - Batch 14, Semarang (Bedakan) - Moersid, Rambo; Faiz, Ahmad (Program Studi Desain Komunikasi Visual, 2024)
The Ministry of Tourism and Creative Economy/Baparekraf is working to provide economic opportunities for 25 creative economy actors. As a part of this effort, the Visual Communication Design Study Program Association (Asprodi) is facilitating an activity that involves its lecturers and students to help strengthen UMKM products, particularly in terms of packaging design. The goal is to find solutions to the packaging-related problems faced by business actors through the study of Visual Communication Design. The method used to achieve this is descriptive qualitative research, which includes data collection through direct discussions with representatives of the Ministry of Tourism and Creative Economy, Asprodi DKV, and related UMKM entrepreneurs. The researchers then created label and initial packaging designs before finalizing the packaging design. As a result of this research, a new label and packaging design for “Sambal Kehidupan” was created.